Measuring and modeling macrophage proliferation in a lab-on-CMOS capacitance sensing microsystem - Smith, Kyle; Lin, Ching-Yi; Gilpin, Yann; Wayne, Elizabeth; Dandin, Marc (Frontiers in Bioengineering and Biotechnology, 2023)
We report on the use of a lab-on-CMOS biosensor platform for quantitatively tracking the proliferation of RAW 264.7 murine Balb/c macrophages. We show that macrophage proliferation correlates linearly with an average capacitance growth factor resulting from capacitance measurements at a plurality of electrodes dispersed in a sensing area of interest. We further show a temporal model that captures the cell number evolution in the area over long periods (e.g., 30 hours). The model links the cell numbers and the average capacitance growth factor to describe the observed cell proliferation.